Solar dryer efficiency considering the total drying potential. Application of this potential as a resource indicator in north-western Argentina - Altobelli, Fabiana Noelia (2014)
Indicators of drying potential for a region based on a model of free water evaporation in a solar dryer are presented. In these indicators, the total solar radiation and the saturation deficit of ambient air are considered as driving forces for solar drying process. The indicators were used to define the solar dryer performance considering the drying potential of the site. The performance definition was applied to a forced solar dryer placed in the town of San Carlos, (Salta, north-western Argentina) and was loaded with 30 kg of trays filled with water. The results were compared with other performance definitions. A standard dryer of 0.1 kg s−1 airflow was defined to estimate the potential indicators for 18 locations of the north-western Argentina using daily historical data. A mapping of dryer potential was obtained for the entire region through interpolating of results, showing similarity in relation to the distribution of phytogeographic areas. September was the month with the highest potential for solar drying on account of the end of the dried season and the influence of the local warm wind. The indicators also were obtained for San Carlos using recently measured data. Deviations from these potentials with respect to those obtained from the historical database were analyzed and similar results were obtained. The usefulness of these indicators was showed as a tool to be considered when variables other than solar radiation – such as temperature and relative humidity – are taken as energy sources.